1997
DOI: 10.1161/01.str.28.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Early Hemorrhage Growth in Patients With Intracerebral Hemorrhage

Abstract: Substantial early hemorrhage growth in patients with intracerebral hemorrhage is common and is associated with neurological deterioration. Randomized treatment trials are needed to determine whether this early natural history of ongoing bleeding and frequent neurological deterioration can be improved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
868
9
47

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,334 publications
(949 citation statements)
references
References 21 publications
25
868
9
47
Order By: Relevance
“…Most intracerebral hematomas that expand do so within the first 24 h, with the majority occurring in the first 6 h of the initial bleed [2]. On noncontrast head CT, fluid levels within the hematoma are associated with coagulopathy and an increased risk of expansion [3].…”
Section: Discussionmentioning
confidence: 99%
“…Most intracerebral hematomas that expand do so within the first 24 h, with the majority occurring in the first 6 h of the initial bleed [2]. On noncontrast head CT, fluid levels within the hematoma are associated with coagulopathy and an increased risk of expansion [3].…”
Section: Discussionmentioning
confidence: 99%
“…Every patient underwent follow‐up head CT in the first 6 to 24 hours. Hematoma expansion was defined as a proportional increase of more than 33% or an absolute increase greater than 6 cc (if baseline ICH volume ≤15 cc) from the initial ICH volume 23. Hydrocephalus was defined as rounding of the frontal horns with increased radius or decreased ventricular angle, increased width of the temporal horns, rounding and enlargement of the atrium with sulcal effacement, increased width of the third ventricle, or ballooning of the fourth ventricle 24.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies also showed increased risks of poor functional outcome and death [16,30,33]. The occurrence of hematoma expansion is related to initial hematoma size; smaller hematomas are less likely to expand [16,34,35].…”
Section: Hematoma Expansionmentioning
confidence: 97%
“…Seventy three percent of patients express some degree of expansion, and 30 to 40% of patients expand more than 33% from baseline volume [13,18,30,31]. The pathophysiological mechanism by which hematoma expansion occurs remains unclear.…”
Section: Hematoma Expansionmentioning
confidence: 99%